2015
DOI: 10.7326/m14-1616
|View full text |Cite
|
Sign up to set email alerts
|

Revisit Rates and Associated Costs After an Emergency Department Encounter

Abstract: Agency for Healthcare Research and Quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 15 publications
6
79
0
2
Order By: Relevance
“…This study is limited to one hospital and significant interhospital variation exists. 1 We are working with other healthcare providers to see if similar patterns hold. Our study demonstrated that there are distinct differences in the determinants for ED revisits among frequent patients and other patients.…”
Section: Discussion and Recommendationsmentioning
confidence: 90%
See 2 more Smart Citations
“…This study is limited to one hospital and significant interhospital variation exists. 1 We are working with other healthcare providers to see if similar patterns hold. Our study demonstrated that there are distinct differences in the determinants for ED revisits among frequent patients and other patients.…”
Section: Discussion and Recommendationsmentioning
confidence: 90%
“…1 Furthermore, the passage of the Affordable Care Act penalizes institutions exceeding set 30-day revisit rates. 2 Many of these ED revisits are seen as preventable, thus a deeper understanding of the phenomenon can help provide streamlined and quality emergency care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, focus on care transitions, post-hospital outpatient care, and corresponding outcomes in the USA has largely been applied to vulnerable older adults discharged from inpatient stays 23 55-58 and to a smaller extent, emergency department stays. 22 34 41 Little attention has been directed to improving outcomes after observation services. Our results suggest that strategies designed to integrate care for patients after discharge from emergency department stays and inpatient stays, such as facilitating access to outpatientproviders, 59 early and longitudinal follow-up, 56 60 61 timely transmittal of information from hospitals to outpatient teams, 62 outpatient availability of care management services, 62 63 multidisciplinary team based care, 64 65 and home visits 66 may also warrant consideration for patients after observation stays, as greater than 90% are discharged home.…”
Section: Discussionmentioning
confidence: 99%
“…6 20 21 This gap in knowledge about observation stays contrasts with the extensive literature describing outcomes after discharge from emergency department treatment-and-discharge stays and inpatient stays. [22][23][24][25] As a result, outstanding questions remain about rates of occurrence of hospital revisits, including emergency department treatment-and-discharge stays, repeat observation stays, inpatient stays, and any hospital revisit after discharge from index observation stays; rates of occurrence of death after discharge from index observation stays; potential differences in revisit and mortality outcomes after discharge from index observation stays compared with outcomes after discharge from index emergency department treatment-and-discharge stays and index inpatient stays; and changes in outcomes over time. These estimates are critical to understanding the vulnerabilities experienced by patients after discharge form observation services and can guide the design of hospital and health system transitional care interventions to mitigate these risks.…”
Section: What This Study Addsmentioning
confidence: 99%